Growth, respiration rates and energetic reserves from a long-term (12-months) multiple driver aquarium experiment with the cold-water coral Desmophyllum pertusum - Kristina K Beck; J Murray Roberts; Zoe Burns; Blair Easton; Sarah Kaye; Marta Peña Fernández; Uwe Wolfram; Sebastian Hennige (PANGAEA, 2025)
We conducted a long-term (12 months) multiple driver aquarium experiment under future environmental conditions at St Abbs Marine Station (UK) with the cold-water coral Lophelia pertusa (syn. Desmophyllum pertusum) sampled from Tisler Reef (Skagerrak). The experiment consisted of four different treatments to investigate the combined effect of ocean acidification, warming, deoxygenation and food limitation on their physiology: 1) control (9 °C, pH 8.1, 100 % oxygen, 100 % food availability), 2) multiple stressor with high feeding (HF; 12 °C, pH 7.7, 90 % oxygen, 100 % food availability), 3) multiple stressor with low feeding (LF; 12 °C, pH 7.7, 90 % oxygen, 50 % food availability) and 4) reduced oxygen (9 °C, pH 8.1, 90 % oxygen, 100 % food availability). Every treatment consisted of three replicate tanks with four live corals (12 in total). Water parameters (temperature, salinity, pH and oxygen concentration) were measured five times per week in every coral tank. The physiological parameters (survival, growth and respiration rate) were determined after 1.5, 3, 4.5, 6, 7.5, 9, 10.5 and 12 months of the experiment. Growth rates were measured using the buoyant weighing technique (Jokiel et al. 1978) with a high precision electronic balance (Pioneer Plus PA224C, OHAUS; precision: 0.1 mg) every 1.5 months. The skeletal dry mass of each coral was calculated from its wet mass and by taking into account the densities of seawater (1.023 ± 0.008 g cm-3) and L. pertusa skeletons (2.747 g cm-3; Naumann et al., 2014). Respiration rates were measured in closed-cell incubations vials in a water bath at the start of the experiment and every 1.5 months. In addition, the energetic reserves (protein, carbohydrate and lipid concentration) of six coral samples per treatment were analysed after 3, 6, 9 and 12 months. The protein, carbohydrate and lipid concentrations were then converted to kilojoules (kJ; protein: 23.9 kJ g-1, carbohydrate: 17.5 kJ g-1, lipid: 39.5 kJ g-1; Gnaiger & Bitterlich, 1984).